Rapid Screening and Quantitative Determination of Active Components in Qing-Hua-Yu-Re-Formula Using UHPLC-Q-TOF/MS and HPLC-UV - Xin Shao; Jie Zhao; Xu Wang; Yi Tao (Journal of Analytical Methods in Chemistry)
Qing-Hua-Yu-Re-Formula (QHYRF), a new herbal preparation, has been extensively used for treating diabetic cardiomyopathy. However, the chemical constituents of QHYRF remain uninvestigated. In the present study, rapid ultrahigh-performance liquid chromatography coupled with quadrupole-time-of-flight mass spectrometry (UHPLC-Q-TOF/MS) was used to qualitatively analyze the components of QHYRF. Qualitative detection was performed on a Kromasil C18 column through the gradient elution mode, using acetonitrile-water containing 0.1% formic acid. Twenty-seven compounds were identified or tentatively characterized, including 12 phenolic acids, nine monoterpene glycosides, two flavonoids, three iridoids, and one unknown compound. Among these, six compounds were confirmed by comparing with standards. A high-performance liquid chromatography (HPLC) method was developed to simultaneously determine the following six active components in QHYRF: danshensu, paeoniflorin, acteoside, lithospermic acid, salvianolic acid B, and salvianolic acid C. These HPLC chromatograms were monitored at 254, 280, and 320 nm. The method was well validated with respect to specificity, linearity, limit of detection, limit of quantification, precision, stability, and recovery. The HPLC-UV method was successfully applied to 10 batches of QHYRF.